Digital Media and the Development of the Arabic Language: the Dynamics of Fusha and Amiyah on the YouTube Digital Platform - Muhammad Ibrohim Futuwwatuddin; Aang Saeful Milah; Lalu Turjiman Ahmad; Ahmad Habibi Syahid (Journal of Educational Sciences, 2026)
This study investigates the dynamics of the use of Modern Standard Arabic (fusha) and colloquial Arabic (amiyah) on YouTube as a digital platform in the context of Arabic language development in the digital media era. The research is based on the phenomenon of diglossia, which characterizes Arab societies, where fusha is traditionally used in formal, educational, and religious contexts, while amiyah is used in everyday communication. The rapid expansion of digital media has reshaped these linguistic boundaries and created new spaces for interaction between the two varieties. This study aims to analyze how language choice on YouTube reflects communicative goals, audience orientation, and sociolinguistic ideology. The research employs a descriptive qualitative method using content analysis with a critical sociolinguistic approach. The data consist of Arabic language YouTube videos categorized into news, opinion, entertainment, and educational content. The findings indicate that fusha is predominantly used in news and educational videos to convey authority and formality, whereas amiyah is more frequently used in opinion and entertainment content to create intimacy and express local identity. The study concludes that Arabic diglossia in digital media is dynamic and context-dependent, with YouTube serving as a space for negotiating linguistic identity, power, and ideology.